Reactive Sputter Deposition - Depla, Diederik; Mahieu, Stijn (Springer Series in Materials Science, 2008)
The use of thin films is continuously expanding. In the family of Physical Vapour Deposition techniques, sputtering is one of the most important over the past 40 years. In this book, all aspects of the reactive magnetron sputtering process, from the discharge up to the resulting thin film growth, are described in detail, allowing the reader to understand the complete process. Hence, this book gives necessary information for those who want to: - start with reactive magnetron sputtering - understand and investigate the technique - control their sputtering process - tune their existing process, obtaining the desired thin films.